Determinación de las Ponderaciones de los Criterios de Sustentabilidad Hidroeléctrica mediante la Combinación de los Métodos AHP y GP Extendida - Gómez Romero, José Andrés; Soto Flores, Rocío; Garduño Román, Susana (Ingeniería, 2019)
Context: Hydropower is a mature and long-lasting technology, but it has presented environmental and social problems. To address these problems, hydropower sustainability initiatives have been created for more than two decades. In Mexico, hydropower projects present environmental and social problems that cause delays in their construction or delays in their entry into operation. The objective of this study was to determine the weightings of the criteria of hydropower sustainability through multicriteria decision-making methods to a group of experts. Method: Through the combination of the multicriteria Analytical Hierarchical Process and the Programming of Goals the opinion of a group of experts was obtained in the planning of hydropower projects. Results: Once the AHP-GP methods were applied to determine the weighting of the hydropower sustainability perspectives, it was found that the weights closest to the opinion of all the groups are those issued by the group of governance experts. Conclusions: The results indicate that, when questioning a heterogeneous group of experts, it was observed that significant agreements are presented between the groups, which is noteworthy because they are groups of experts that have different specialties.